Developing creative service industries in Hangzhou, China - Wen, W.; Keane, Michael (OECD Publishing, 2014)
Creativity is changing the People’s Republic of China according to Li Wuwei (2011), a leading Chinese economist and policy advisor. The nation is learning to embrace a "third industrial revolution" (Rifkin, 2011) while banking the economic capital of the carbon-dependent manufacturing economy. Urbanisation is also driving change and consumer culture (Gerth, 2010).